Audit Opinions and Auditor Switching under Management Change - Benny Oktaviano; Ahmad Bukhori Muslim (Jurnal Akuntansi Bisnis Pelita Bangsa, 2025)
This study investigates how audit opinions affect auditor switching and management change in listed companies using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Unfavorable or modified audit opinions often create management dissatisfaction, potentially driving decisions to replace auditors or restructure leadership. Using firm data analyzed through bootstrapping for path significance, the findings reveal that audit opinion positively and significantly influences auditor switching (β = 0.215; p = 0.012) and negatively affects management change (β = −0.134; p = 0.037). In contrast, auditor switching shows a positive and significant relationship with management change (β = 0.289; p = 0.000). These results highlight that audit opinions are a key determinant of organizational shifts, directly and indirectly shaping managerial and auditor transitions. The findings underscore the importance of transparent reporting in maintaining organizational stability.